AB0667 Pregnancy outcomes in a tertiary takayasu arteritis care centre. (12th June 2018) - Szabo, I.E.; Tamas, M.M.; Damian, L.; Filipescu, I.; Dobrota, I.; Rednic, S.
Abstract : Background: Fertility and pregnancy are concerning issues in women of childbearing age with Takayasu arteritis (TA). Available data on the management and expected events in TA during pregnancy are sparse and inconsistent among study populations 2, 3 . Conflicting reports exist on both favourable pregnancy outcomes as well as increased fetal or maternal complications 1, 4 . Objectives: To assess the obstetric and maternal outcomes in a tertiary centre TA cohort. Methods: 15 female patients fulfilling the American College of Rheumatology 1990 criteria for the classification of TA were included in this retrospective study. Data regarding number of pregnancies, disease characteristics and pregnancy related events were gathered from medical records. Disease extent was classified according to Numano classification criteria for TA: type I (4 patients, 26.66%), type III (4 patients, 26.66%), type V (3 patients, 20%), type IV (2 patients, 13.33%), type IIa (1 patient, 6.66%), type IIb (1 patient, 6.66%). The prevalence of obstetric and maternal complications was evaluated in women before or after TA diagnosis. 6 patients were further excluded due to the paucity of information concerning pregnancy outcomes. Results: A total of 15 pregnancies were identified in 9 patients, with 9 (60%) occurring before TA diagnosis – group 1, and 6 (40%) occurring concomitant with or after TA diagnosis – group 2. In the first group the extent of arterial involvement was mostly consistent with type I TA (6 pregnancies, 66.66%). No fetal or maternal complications were observed in this group. Type III TA was most commonly encountered (4 pregnancies, 66.66%) in group 2. Only one patient from the second group had more than 1 pregnancy after TA diagnosis. Active disease (National Institutes of Health/NIH score >1) was reported in 2 (33.33%) pregnancies in the second group. Cardiovascular events occurred exclusively during 2 (33.33%) pregnancies exhibiting active disease. One patient suffered severe aortic regurgitation and gestational hypertension during pregnancy, while the second patient experienced worsening of preexisting hypertension. These required steroid dose increase and addition of antihypertensive drugs. There were no obstetric events in group 2. Conclusions: Most TA pregnancies are uneventful, bearing favourable fetomaternal outcomes. However, pregnant TA patients with active disease, have higher risk of developing maternal complications, especially cardiovascular events. In this setting, close monitoring and disease remission should be maintained during pregnancy. References: [1] Tanaka H, Tanaka K, et al. Analysis of pregnancies in women with Takayasu arteritis: Complication of Takayasu arteritis involving obstetric or cardiovascular events. J Obstet Gynaecol Res. 2014Sep;40(9):2031–6. [2] Gudbrandsson B, Wallenius M, et al. Takayasu arteritis and pregnancy; – a population based study on outcome and mother child related concerns. Arthritis Care Res (Hoboken). 2017Sep;69(9):1384–1390. [3] Assad AP, da Silva TF, et al. Maternal and Neonatal Outcomes in 89 Patients with Takayasu Arteritis (TA): Comparison Before and After the TA Diagnosis. J Rheumatol. 2015Oct;42(10):1861–4. [4] Comarmond C, Mirault T, et al. Takayasu Arteritis and Pregnancy. Arthritis Rheumatol. 2015Dec;67(12):3262–9. Disclosure of Interest: None declared